1998
DOI: 10.1111/j.1479-828x.1998.tb02954.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Glyceryl Trinitrate for Uterine Relaxation at Caesarean Section—a Prospective Trial

Abstract: We report a prospective study on the use of sublingual glyceryl trinitrate at Caesarean section to induce uterine relaxation; 23 women were entered into the study with both emergency and elective cases considered. A metered dose spray was used to deliver a dose of 400 or 800 microgrammes of glyceryl trinitrate to the women. There were no major side-effects of hypotension or postpartum haemorrhage. The mean maximal systolic blood pressure drop in the patients following drug administration was 18% of the systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…One patient who received two doses of 50 g of NTG subsequently required a blood transfusion for excessive blood loss in a case complicated by a uterine inversion (Altabef et al 4 ). Postpartum hemorrhage (Craig et al 25 ) and hypotension (Chan et al, 23 Bayhi et al, 3 Mercier et al 6 ) were more commonly observed in parturients receiving initial doses of Ͼ400 g NTG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One patient who received two doses of 50 g of NTG subsequently required a blood transfusion for excessive blood loss in a case complicated by a uterine inversion (Altabef et al 4 ). Postpartum hemorrhage (Craig et al 25 ) and hypotension (Chan et al, 23 Bayhi et al, 3 Mercier et al 6 ) were more commonly observed in parturients receiving initial doses of Ͼ400 g NTG.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive alternative to i.v. dosing may be the use of the NTG metered dose sublingual spray (Redick and Livingston, 13 Greenspoon and Kovacic, 17 Dalton and Ray, 9 Craig et al, 25 Dawson and Gabbot 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies, a total of 89 patients received GTN during elective caesarean section as a means of achieving uterine relaxation 6,7 . Maternal and fetal effects were also evaluated.…”
Section: Case Reviewsmentioning
confidence: 99%
“…The uterus is a smooth muscle organ and nitro-vasodilators such as amyl nitrate have been used to achieve rapid uterine relaxation for over a century [1][2][3] . The use of GTN to achieve rapid uterine relaxation during obstetric emergencies has generated many observational studies [4][5][6][7][8][9][10][11][12][13][14][15][16] and case reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] in the anaesthetic and obstetric literature. The ability to achieve simple, reliable and rapid uterine relaxation is of particular interest to the anaesthetist, as this would lessen the need to subject the parturient to the risks of anaesthesia.…”
mentioning
confidence: 99%